Salvaging Buildings Reclaiming a Livelihood from the Excesses of Istanbul's Mass Urbanization - Ceritoglu, Erdogan Onur (Architekturen, 2023)
For at least two decades, major cities in Turkey have been subjected to endless waves of urban development that has left scores of building demolitions in its wake. The construction waste produced is immense but its removal or abatement is completely ignored by the state. Who will deal with all this waste? Enter the reclaimers (çkmacs), an informal network of building salvagers, who have stepped in to create a new form of assemblage that fills this gap. Erdogan Onur Ceritoglu makes an in-depth ethnographic study of the under-the-radar livelihood of the reclaimers long-term. He also focuses on incremental architecture through the reuse of second-hand building elements.